2017
DOI: 10.1091/mbc.e16-04-0228
|View full text |Cite
|
Sign up to set email alerts
|

Local Arp2/3-dependent actin assembly modulates applied traction force during apCAM adhesion site maturation

Abstract: In growth cones, local Arp 2/3-dependent actin assembly mechanically buffers apCAM adhesions from retrograde flow–associated traction forces. The resulting propulsive forces drive the exploratory motility of inductopodia. Increasing the stiffness of apCAM targets induces an extensive 3D actin cup to form at the adhesion during evoked growth responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Interestingly, the integrin-activating adaptor protein kindlin-2 (Fermt2) interacts with paxillin to activate Rac1 and associates with the Arp2/3 complex to induce membrane protrusions ( Böttcher et al, 2017 ). Local Arp2/3-dependent actin polymerisation may thus regulate efficient traction force application, buffering nascent adhesions from the mechanical effects of retrograde flow ( Buck et al, 2017 ). Arp2/3-depleted fibroblasts failed to properly align focal adhesions ( Wu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the integrin-activating adaptor protein kindlin-2 (Fermt2) interacts with paxillin to activate Rac1 and associates with the Arp2/3 complex to induce membrane protrusions ( Böttcher et al, 2017 ). Local Arp2/3-dependent actin polymerisation may thus regulate efficient traction force application, buffering nascent adhesions from the mechanical effects of retrograde flow ( Buck et al, 2017 ). Arp2/3-depleted fibroblasts failed to properly align focal adhesions ( Wu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…73 However, a reasonable prediction is that different ECM pre-gels, even below gelation concentrations, could have distinct mechanical and physical compositions that could regulate growth. 74 Mechanical or physical changes that alter substrate adhesions patterns, 75 adhesion signaling, 76 mechanical forces on adhesion sites, 77 and/or the traction forces generated between substrate adhesions and the cytoskeleton 78 would all be expected to alter neurite growth and warrant further study. During ECM injection, ECM factors can penetrate CNS tissues prior to gelation, exposing neurons and other cells to both soluble and insoluble ECM factors.…”
Section: Discussionmentioning
confidence: 99%
“…The third subtype of F-actin structures are the transverse actin arcs that surround the central domain and control its shape as well as the distribution of MTs ( Schaefer et al, 2002 , 2008 ; Zhang et al, 2003 ). Lastly, the fourth F-actin structure is the dynamically rearranging intrapodia or ruffles in the transition zone ( Rochlin et al, 1999 ), which recently have been suggested to promote traction force generation by buffering developing adhesion sites from the effects of retrograde flow ( Buck et al, 2017 ).…”
Section: Neuronal Structurementioning
confidence: 99%